Improvement in self-assessed knowledge and changes in farming system practices of climate field school graduates in Bicol, Philippines - Ruelos, Ruth Anne T. (The Journal of Public Affairs and Development, 2017)
Rainfed lowland and upland farmers have less access to new technologies especially those that would reduce their vulnerability to climate change. In the Philippines, the Philippine Rice Research Institute developed a package of technology called "Palayamanan" that is suited to rainfed sites. This paper presents the results of the study that disseminated the Palayamanan technology through the climate field school (CFS) in rainfed areas in Bicol. Thirty-eight farmers from two barangays Pamplona, Camarines Sur, and 78 farmers from three barangays of Milagros, Masbate were the respondents. A five-point scale was used to self-assess farmers' knowledge on topics discussed in the CFS, which were divided into four major parts: climate: climate science, rice production, vegetable and animal production, and pest and water management. Weighted means of the farmers' self-assessed knowledge scores before and after the CFS were generated. The Mann-Whitney U method was used to test the significance of the differences in the pre-and post-test scores. The differences between pre- and post-test scores were highly significant (at 5% level), especially on the clustered topics of climate, land preparation and seedling establishment, soil nutrient management, pest management, and harvesting.